Responsible research in health disparities using the Adolescent Brain Cognitive DevelopmentSM (ABCD) study - MR Gonzalez; C Cardenas-Iniguez; DE Linares; S Wonnum; K Bagot; EJ White; A Cuan; S DiMatteo; YD Akiel; P Lindsley; JC Harris; E Perez-Amparan; et al. (Developmental Cognitive Neuroscience)
Purpose: The Adolescent Brain Cognitive DevelopmentSM (ABCD) Study is the largest longitudinal study on brain development and adolescent health in the United States. The study includes a sociodemographically diverse cohort of nearly 12,000 youth born 2005–2009, with an open science model of making data rapidly available to the scientific community. The ABCD Study® data has been used in over 1100 peer-reviewed publications since its first data release in 2018. The dataset contains a broad scope and comprehensive set of measures of youths’ behavioral, health, and brain outcomes, as well as extensive contextual and environmental measures that map onto the social determinants of health (SDOH). Understanding the impact of SDOH on the developmental trajectories of youth will help to address early lifecourse health inequities that lead to disparities later in life. However, the open science model and extensive use of ABCD data highlight the need for guidance on appropriate, responsible, and equitable use of the data. Design Methods: Our conceptual framework integrates the National Institute on Minority Health and Health Disparities (NIMHD) Research Framework with strength-based and data equity perspectives. We use this framework to articulate best practices and methods for investigations that aim to identify the multilevel pathways by which structural and systemic inequities impact adolescent health trajectories. Results: Using our conceptual model, we provide recommendations for equitable health disparities research using ABCD Study data. We identify over fifty ABCD measures that can encompass SDOH across five levels of influence: individual, interpersonal, school, community, and societal. We expand the societal level to acknowledge structural discrimination as the root cause of systemic and structural inequities resulting in health disparities among marginalized youth. We apply the methodological recommendations in an example data analysis using a multi-level approach that integrates strength-based and data equity perspectives to elucidate pathways by which social and structural inequities may influence cognitive decision making in youth. We conclude with recommendations for strengthening the utility of ABCD data for health disparities research now and in the future. Conclusion: Adolescence is a critical period of development with subsequent ramifications for health outcomes across the lifespan. Thus, understanding SDOH among diverse youth can inform prevention interventions before the emergence of health disparities in adulthood.